Analisis Pengaruh Profitabilitas, Likuiditas, Ukuran Perusahaan dan Struktur Modal Terhadap Nilai Perusahaan - Danisya Zalza Billa Putri Supriyanto; Zaky Machmuddah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study examines the relationship between firm value (Tobin's Q) and profitability (ROA), liquidity (CR), company size (SIZE), and capital structure (DER). Using a purposive selection technique, we examined a sample of 60 industrial enterprises that were listed on the Indonesia Stock Exchange (IDX) between 2021 and 2023. Using IBM SPSS 26, we performed a multiple linear regression analysis, which showed that each of these characteristics had a significant impact on the value of the company.